Nether Station - Anderson, Kevin J., 1962- (Blackstone Publishing, 2024)
Astrophysicist Cammie Skoura has joined the first research team traveling to the Nether anomaly, eager to understand the mechanics of the wormhole and to explore its possibilities as a shortcut to Alpha Centauri. But another race of ancient beings has already been here, an impossibly long time ago, leaving remnants of their vast complexes and gigantic temples built for horrific beings beyond comprehension. Cammie and the crew of Nether Station must find the answers before the darkest part of the cosmos swallows them up.